Extending post-harvest quality of fresh fig (Ficus carica L.) fruit through manipulation of pre- and post-harvest practices: a review - Nur Athirah Mat Jusoh,; Ding, Phebe; Choon, Sea Yeat (Penerbit Universiti Kebangsaan Malaysia, 2020)
Fresh fig fruit has a very unique taste. However, it is well-known as very perishable climacteric fruit. The various factors that involve during the pre-harvest and post-harvest handling processes have caused great challenges to farmer in maintaining the keeping quality of fresh fruits. The key factors involve are disease, water supply, fertilizer management, fruit maturity at harvest as well as post-harvest handling. Thus, good pre- and post-harvest practices are very important in improving the storage quality of fresh fig fruit. In this article, the studies on improving the storage life of fig fruit including the practices used during pre- and post-harvest handling of fig fruit were reviewed. For pre-harvest practices, deficit irrigation, application of plant growth regulator (1-methylcyclopropene) and pollination were applied to improve the quality of fresh fig fruit. For post-harvest treatments, coating, modified atmosphere packaging and optimizing the storage temperature and relative humidity were used in keeping the post-harvest quality of fresh fig fruit.